Public relations planning : a practical guide for strategic communication - Vieira, Edward T., Jr.; Li, Yulong (New York, NY : Routledge, 2024)
"Public Relations Planning: A Practical Guide for Strategic Communication provides students with an in-depth understanding of the steps involved in planning and executing a successful PR campaign. Taking a strategic approach to the subject, the authors bring years of practical experience to the project, helping students see how theoretical elements fit together in reality and preparing them for the workplace. At the same time, the book goes beyond an introductory discussion of the theory of PR planning, incorporating material from cutting-edge research in the field. This fully updated second edition explores current trends and consequences surrounding the COVID-19 pandemic; covers the latest technological tools and techniques, as well as the ever-changing landscape of social media; and examines the role of data analytics in the PR decision-making process. Examples and vignettes have been updated so that they reflect the current state of the global PR environment, whilst learning objectives, key term definitions and chapter exercises facilitate comprehension. Providing a solid foundation to the PR planning process, this text is core reading for advanced undergraduate, postgraduate and executive education students studying Public Relations Strategy, Public Relations Campaigns, and Strategic Communications. Online resources include PowerPoint lecture slides, a test bank, answers for end-of-chapter questions, and instructor notes for the case studies. Public Relations Planning is featured on the International Public Relations Association web site"--
Keywords: Public relations; Strategic planning; Social media; BUSINESS & ECONOMICS / Public Relations; BUSINESS & ECONOMICS / Business Communication / General